2021
DOI: 10.1177/22779752211000479
|View full text |Cite
|
Sign up to set email alerts
|

Does the Dark Side of Personality Traits Explain Compulsive Smartphone Use of Higher Education Students? The Interaction Effect of Dark Side of Personality with Desirability and Feasibility of Smartphone Use

Abstract: Research on compulsive use of smartphones amongst students largely remains unexplored. The study seeks to investigate the feasibility and desirability motives—instant gratification, mood regulations, convenience, flow and personality—to understand the compulsive use of smartphones. The results of the useful data of 200 respondents following purposive sampling design, provided evidence of instant gratification, mood regulation and convenience motives, which significantly explain flow and compulsive smartphone u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 90 publications
0
6
0
1
Order By: Relevance
“…Consumers would not adopt the innovation if they found difficulty in using that specific technology (Banu et al, 2019;Hassan & Wood, 2020). Past studies have shown a positive impact of PEOU on the adoption of different innovations (Aslam, Tariq, et al, 2019;Farhat et al, 2021;Hanafizadeh et al 2014;Mehrad & Mohammadi, 2017;Mohammadi, 2015;Purohit & Arora, 2021;Sharma, 2019). The theory of TAM also postulates that the usefulness of the technology drives the adoption.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Consumers would not adopt the innovation if they found difficulty in using that specific technology (Banu et al, 2019;Hassan & Wood, 2020). Past studies have shown a positive impact of PEOU on the adoption of different innovations (Aslam, Tariq, et al, 2019;Farhat et al, 2021;Hanafizadeh et al 2014;Mehrad & Mohammadi, 2017;Mohammadi, 2015;Purohit & Arora, 2021;Sharma, 2019). The theory of TAM also postulates that the usefulness of the technology drives the adoption.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Finally, the present study underscores the importance of giving autonomy to the faculty that enables them to craft the jobs to match their skills and abilities to complete assigned tasks. Furthermore, in the present-day digital world, most students are habituated to mobile devices and can attend online classes; more important is to see the compatibility of operating systems that are user-friendly (Farhat et al, 2022). The leaders of higher education institutions need to understand that it is important to provide adequate technological infrastructure for successful functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these testimonies highlight the importance and need for sport management education programs to provide students with adequate training in the use of digital technologies, as requested by authors such as López-Carril et al [39] and Pate and Bosley [52]. Despite this, we must be cautious about how we teach how to use these technologies, as they also have a "dark side" that can negatively impact students' habits and health [53]:…”
Section: Changes In Personal Habits and New Skills Developmentmentioning
confidence: 99%